2019
DOI: 10.1039/c9dt00878k
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent Ru(ii)-thiol modified silver nanoparticles for lysosome targeted theranostics

Abstract: AgNPs modified by Ru(ii) complexes possess bright red fluorescence and may act as potential lysosome-targeted theranostic agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…This indicated that the casticin-loaded nanoemulsion entered the lysosome after cellular uptake but did not enter the nucleus. Many studies have shown that nanomaterials enter cells through endocytosis to form endosomes and then are accumulated in lysosomes [ 27 ]. Kam et al labeled single-walled carbon nanotubes (SWNT) and co-cultured them with HL60 cells.…”
Section: Resultsmentioning
confidence: 99%
“…This indicated that the casticin-loaded nanoemulsion entered the lysosome after cellular uptake but did not enter the nucleus. Many studies have shown that nanomaterials enter cells through endocytosis to form endosomes and then are accumulated in lysosomes [ 27 ]. Kam et al labeled single-walled carbon nanotubes (SWNT) and co-cultured them with HL60 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Two of these Ru complexes, Ru32 and Ru33, were also used by Shi and co-workers for functionalization of silver nanoparticles (AgNPs), resulting in monodisperse and homogeneous spherical nanoparticles with an average diameter of 20 nm. [71] AgNPs are known to induce cytotoxicity by an excessive generation of reactive oxygen species (ROS). Functionalization with Ru(II) complexes allowed cell imaging and enhanced anticancer activity.…”
Section: Gold and Silver Nanoparticlesmentioning
confidence: 99%
“…[37][38][39] On the contrary, in the passive targeting approach, the nature of the tumor tissue is tackled through their poor lymphatic tissue and leaky, highly permeable vasculature properties, also referred to as the enhanced permeability and retention (EPR) effect, 40 although this concept is currently controversially discussed based to its limitations in in vivo models. 41 Examples involve the encapsulation into polymeric particles, [42][43][44][45][46][47] liposomes [48][49] or functionalization of nanoparticles based on silver, 50 gold, 51 selenium, [52][53] or silica. [54][55][56] Within this context, some attention has been focused on the application of mesoporous silica nanoparticles (MSNs) due to their low price, synthetic accessibility as well as tumor targeting properties.…”
Section: Introductionmentioning
confidence: 99%
“…In the active targeting approach, a specific biological interaction is utilized like signaling peptides, , oligonucleotides, , oligosaccharides, vitamins, , proteins, , antibodies, or receptor targeting moieties. On the contrary, in the passive targeting approach, the nature of the tumor tissue is tackled through their poor lymphatic tissue and leaky, highly permeable vasculature properties, also referred to as the enhanced permeability and retention (EPR) effect, although this concept is currently controversially discussed based on its limitations in in vivo models . Examples involve the encapsulation into polymeric particles, liposomes, , or functionalization of nanoparticles based on silver, gold, selenium, , or silica. …”
Section: Introductionmentioning
confidence: 99%